Pengaruh Lingkungan Kerja Non Fisik dan Motivasi Kerja terhadap Kinerja Karyawan pada Petugas Teknik PT. XYZ - Octarina, Jasmine Aulia; Khaerul Rizal Abdurahman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of non-physical work environment and work motivation on employee performance in engineering officers of PT. XYZ Cimahi. The research method used is a quantitative descriptive and associative approach with data collection techniques through questionnaires, interviews, and documentation. Respondents in this study consisted of 41 engineering officers and 1 direct superior. The results of the study indicate that both non-physical work environment and work motivation have a positive effect partially and simultaneously on employee performance. The results of multiple regression tests indicate that non-physical work environment has the most significant effect on performance. Validity, reliability, and classical assumption tests support the validity of the data, with a coefficient of determination of 96.2%. The conclusion of this study is that improving the quality of non-physical work environment and work motivation can significantly improve employee performance. Keywords: Non-Physical Work Environment, Work Motivation, Employee Performance